The Different Concept Of Positive And Negative Politeness Of Brown And Levinson Toward Indonesian Language Through Second Person Pronoun Analysis - Agung Tri Wahyuningsih (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2019)
This article is trying to see the great difference of positive and negative politeness concept proposed by Brown and Levinson by looking at different second person pronouns of English and Indonesian language. Politeness which ties the use of language universally exists in any language, though the concept is uniquely different. Brown and Levinson’s (1987) proposition of the concept of politeness, despite fruitfully enriching our understanding, could not escape criticism of several points one of which is the relevance of cultural norm. Cultural norm relying substantially on the language use, therefore, governs the people’s use of the language appropriately and properly which necessitates the interplay between dictions and meaningful context. In short, this article will review one marker of politeness, i.e. second person pronouns in English and Indonesian to reveal the great difference in running politeness strategies.